Combination of plant phenolics and isoquinolinium alkaloids protects gingival fibroblast and improves post-extraction healing after lower third molar extraction - Chytilová, Karin; Galandáková, Adéla; Valentová, Kateřina; Tvrdý, Peter (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2023)
AIMS: The effect of polyphenolic fraction of Lonicera caerulea (PFLC) and alkaloid fraction of Macleaya cordata (AFMC) mix on the production of inflammatory mediators in human gingival fibroblasts pretreated with lipopolysaccharide (LPS) was investigated. In addition, protective effects of mucoadhesive paste containing combination of PFLC and AFMC (0.05% and 0.01%, respectively; n=15, Group A) and placebo (n=15, Group B) were evaluated in patients after surgical extraction of lower third molars. METHODS: Gingival fibroblasts were pre-treated with LPS (10 μg/mL; 24 h) and PFLC/AFMC (25/0.25; 50/0.25; 100/0.25; 25/0.5; 50/0.5; 100/0.5 μg/mL) in serum-free medium was applied for 4 h. Then the interleukin-6 (IL-6), reactive oxygen species (ROS) generation, level of intracellular glutathione (GSH) and expression of cyclooxygenase-2 (COX-2) were evaluated. The study was a 6-day, single-center, randomized, double-blind and placebo-controlled trial consisting of two parallel treatment arms. A modified Oral health impact profile questionnaire including both general oral condition and extraction related questions, was used to evaluate the oral condition and other changes before (day 0) and on the days 1, 3 and 6 after surgical extraction. RESULTS AND CONCLUSION: The combination of PFLC with AFMC caused a reduction of ROS generation, reduced IL-6 production and suppressed the expression of COX-2. In group A the paste treatment contributed to improvement of oral health-related quality of life. Topical application of PFLC and AFMC into the extraction wound improved post-extraction site wound healing probably by antioxidant and anti-inflammatory mechanisms.
Keywords: Wound Healing; cyklooxygenasa 2; Humans; Phenols; fenoly; Cyclooxygenase 2; alkaloidy; Lipopolysaccharides; molár třetí; Reactive Oxygen Species; lipopolysacharidy; Molar, Third; reaktivní formy kyslíku; Alkaloids; interleukin-6; lidé; hojení ran; fibroblasty; Quality of Life; Fibroblasts; Interleukin-6; kvalita života